Philosophy of (for) the Conquest. Eurocentrism and Colonialism in the Dispute for the New World [Filosofía de (Para) la Conquista. Eurocentrismo y Colonialismo en la Disputa por el Nuevo Mundo] - Santos-Herceg, J (2011)
This paper aims to demonstrate that the discussion "about" the Conquest of America -known as the Philosophy of the Conquest- as well as the reflections of the most famous thinkers who participated in the debate -Juan Ginés de Sepúlveda, Francisco de Vitoria and Bartolomé de las Casas- can be characterized as being eurocentric and colonialist. This is the reason why it would be preferable to speak of a philosophy "for" the conquest instead of a philosophy "of" or "about" the conquest.
Keywords: Colonialism; Conquest; Eurocentrism; Latin America